Efektivitas menggunakan pajak minuman manis untuk mengurangi obesitas: tinjauan sistematis - Widi Astutty Casimira Daeli; Atik Nurwahyuni (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
The effectiveness of taxes on sugar-sweetened beverages to reduce obesity: a systematic reviewPurpose: Use of taxes on Sugar-Sweetened Beverages (SSBs) can contribute to reducing the prevalence of obesity. However, how much effectiveness needs to be proven. Method: A systematic review was carried out on articles published between 2013-2018, which examined the effectiveness of the SSBs tax to prevent obesity. Results. Five relevant studies were included in this review. One study discussed the effectiveness of SSBs tax to provide benefits for saving health care costs. Two studies concluded that the tax for consumption and the purchase of SSBs decreases and had an impact on weight loss. Finally, two other studies reported the effectiveness of SSBs tax in more detail to decreasing DALYs and increasing QALYs, which can save health care costs. Conclusion: The application of a 20% SSBs tax is effective for reducing excess weight, increasing QALYs, and decreasing DALYs. SSBs tax should consider different countries consumer behavior in substituting and complementing other beverage products containing sweeteners.